Personality factors, money attitudes, financial knowledge, and credit card debt among working adults in Kelantan / Siti Syahirah Mohd Zari - Mohd Zari, Siti Syahirah (2013)
The purpose of the study is to investigate the influence of personality factors, money attitude, financial knowledge and credit card debt among working adults in Kelantan. This study is scoped out by distribute questionnaire among working adults in Kelantan. Only 120 questionnaires were distribute among working adults in Kelantan. The credit card debt is dependent variable while personality factors, money attitude and financial knowledge have been choose as independent variables in this study. Based on findings, only financial knowledge is found to be significant relationship toward credit card debt, while money attitude and personality factors are insignificant. In short, only financial knowledge has significant toward credit card debt among working adults in Kelantan, while another variable is insignificant